ScratchAnalytics: Um Framework para Coleta e Análise de Interações em Projetos Scratch - Vaz Junior, Jorge Luis Nachtigall; Primo, Tiago Thompsen; Pernas, Ana Marilza (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2020: Anais do XXXI Simpósio Brasileiro de Informática na Educação, 2020)
Technological advancement and its impact on our lives gradually highlights the need to use technological resources in the educational environment. One of these resources is Scratch, a block programming tool, widely used in educational projects which aim to provide students with the teaching of programming from a creative and constructionist perspective. As a result, evaluations and validations become necessary, in order to provide more information on the impact generated by these projects. This work presents a proposal to facilitate the execution of these analyzes, through the implementation of a framework which automates the process of collecting and analyzing interactions made by students in Scratch.